2021
DOI: 10.5187/jast.2021.e12
|View full text |Cite
|
Sign up to set email alerts
|

Wheat phytase can alleviate the cellular toxic and inflammatory effects of lipopolysaccharide

Abstract: The objective of this study was to characterize the enzymatic hydrolysis of lipopolysaccharide (LPS) by wheat phytase and to investigate the effects of wheat phytase-treated LPS on in vitro toxicity, cell viability and release of a pro-inflammatory cytokine, interleukin (IL)-8 by target cells compared with the intact LPS. The phosphatase activity of wheat phytase towards LPS was investigated in the presence or absence of inhibitors such as L-phenylalanine and L-homoarginine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Importantly, Ca and P retention was not decreased by Ca/P in the 6-11, 11-25, and 25-50 kg BW categories; this explains the linear increase in ADG with increasing Ca/P. Digestibility of Ca in pig production is not only affected by Ca level, but also by the exogenous phytase and Ca/P to which the pigs are subjected, as well as the growth stage [5,18]. For pigs, the aim is to optimize BW while decreasing Ca excretion.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Importantly, Ca and P retention was not decreased by Ca/P in the 6-11, 11-25, and 25-50 kg BW categories; this explains the linear increase in ADG with increasing Ca/P. Digestibility of Ca in pig production is not only affected by Ca level, but also by the exogenous phytase and Ca/P to which the pigs are subjected, as well as the growth stage [5,18]. For pigs, the aim is to optimize BW while decreasing Ca excretion.…”
Section: Discussionmentioning
confidence: 90%
“…Digestibility of Ca in pig production is not only affected by Ca level, but also by the exogenous phytase and Ca/P to which the pigs are subjected, as well as the growth stage [ 5 , 18 ]. For pigs, the aim is to optimize BW while decreasing Ca excretion.…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that wheat phytase could enhance cell viability of HT-29 against UDP-induced cytotoxicity by upregulating the release of both IL-6 and IL-8 known to be associated with proliferation and survival of many cells [ 24 , 25 ]. The present study also focuses on the possibility that wheat phytase may function as a direct up-regulator of IL-6 or IL-8 expression like HSP60 (heat shock protein 60) to enhance the cell survival against ATP or UDP stimulus [ 27 ], which is a new approach different from our previous studies that the enzyme play a role in decreasing the IL-8 release for cell viability against phosphorylated substrates such as LPS (lipopolysaccharide) and inorganic polyphosphates, mainly derived from exogenous pathogenic bacteria [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%